2019
DOI: 10.1002/mgg3.624
|View full text |Cite
|
Sign up to set email alerts
|

Association between ADIPOQ G276T and C11377G polymorphisms and the risk of non‐alcoholic fatty liver disease: An updated meta‐analysis

Abstract: Background Nonalcoholic fatty liver disease (NAFLD) is a significant contributor to global hepatic disorders. ADIPOQ gene single‐nucleotide polymorphisms have been associated with NAFLD susceptibility, but with inconsistent results across the studies. This study aimed to investigate the association between ADIPOQ polymorphisms (+276G>T, rs1501299 and −11377C>G, rs266729) and the risk of NAFLD. Methods PubMed, Embase,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
(35 reference statements)
1
6
0
Order By: Relevance
“…NAFLD is a multiple factor disease that is influenced by genetic variation, diet, age, sex, ethnicity, and lifestyle, along with conditions including obesity, insulin resistance, dyslipidemia, hypertension, diabetes mellitus, and metabolic syndrome ( Hamabe et al, 2011 ; Satapathy and Sanyal, 2015 ; Kalia and Gaglio, 2016 ; Tong and Guo, 2019 ; Zhang et al, 2019 ). Several studies have been conducted on the association between gene polymorphism and NAFLD ( Kong et al, 2017 ; Liu et al, 2019 ; Xu et al, 2019 ). Specifically, some studies have indicated that susceptibility genes may play an important role in the pathogenesis of NAFLD ( Sookoian and Pirola, 2011 ; Yang et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…NAFLD is a multiple factor disease that is influenced by genetic variation, diet, age, sex, ethnicity, and lifestyle, along with conditions including obesity, insulin resistance, dyslipidemia, hypertension, diabetes mellitus, and metabolic syndrome ( Hamabe et al, 2011 ; Satapathy and Sanyal, 2015 ; Kalia and Gaglio, 2016 ; Tong and Guo, 2019 ; Zhang et al, 2019 ). Several studies have been conducted on the association between gene polymorphism and NAFLD ( Kong et al, 2017 ; Liu et al, 2019 ; Xu et al, 2019 ). Specifically, some studies have indicated that susceptibility genes may play an important role in the pathogenesis of NAFLD ( Sookoian and Pirola, 2011 ; Yang et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…ADIPOQ (adiponectin) is an adipose-derived plasma protein that functions in hepatic lipoprotein-lipid metabolism [ 70 ]. Several pieces of evidence indicate that diverse polymorphisms in ADIPOQ may increase susceptibility to NAFLD [ 70 , 71 ]. One study reported that the ADIPOQ methylation rate in rats with NAFLD was higher than in control animals [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Several studies have investigated the association between gene polymorphisms and NAFLD. [8][9][10][11] Acetaldehyde dehydrogenase 2 (ALDH2) is an enzyme involved in redox homeostasis and hepatic ethanol metabolism. 12,13 The rs671 polymorphism (also named Glu504Lys) has been the most commonly studied.…”
Section: Introductionmentioning
confidence: 99%